2022
DOI: 10.51985/jbumdc202234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ideal Learning Style among Medical Students using VARK Learning Approach

Abstract: Objective: Learning styles are important in the learning process so that students can learn in shorter time according to their preferred style. The objective of this study is to observe ideal preferred learning style among medical students and the association of the academic year with the preferred learning style. Study Design and Setting: A cross-sectional study was conducted at Central Park Medical College, Lahore, Pakistan from September 2021 to December 2021. Methodology: VARK learning approach was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…18 A study conducted at Central Park Medical College, Lahore, and another study conducted in Iran found that the learning preferences of the students and their academic years are strongly associated. 15,19 In our study, we also found that students in the preclinical and clinical stages had significantly different learning styles. A study suggested that the preclinical curriculum involves theoretical instructional strategies majorly, while clinical students are likely to have a learning style involving the psychomotor domain.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…18 A study conducted at Central Park Medical College, Lahore, and another study conducted in Iran found that the learning preferences of the students and their academic years are strongly associated. 15,19 In our study, we also found that students in the preclinical and clinical stages had significantly different learning styles. A study suggested that the preclinical curriculum involves theoretical instructional strategies majorly, while clinical students are likely to have a learning style involving the psychomotor domain.…”
Section: Discussionsupporting
confidence: 58%
“…14 Contrary to it, two studies conducted in Lahore reported that there is a significant difference in learning style preferences among male and female medical students. 2,15 Our statistical data showed that the students in the sample who were 21 years old, most of them preferred the kinesthetic learning style (37 out of 60 students), whereas a review study, which explored learning styles across the globe, showed that age factor has no relationship with learning styles. 17 It included postgraduate and undergraduate medical students, while our study was conducted among undergraduate students.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…One of the most popular is the VARK Questionnaire created by Fleming and Baume. The estimated high validation and reliability of the VARK Questionnaire make it one of the widest used approaches [14].…”
Section: Original Article Open Accessmentioning
confidence: 99%